Allelopathic suppression of weeds in rice field by Tinospora tuberculata beumee - Aslani, Farzad (2015)
Herbicides produce a wide range of toxic side-effects that pose a potential hazard to the environment. The development of natural herbicide is one method of addressing these issues. Tinospora tuberculata is an aromatic shrub with pharmacological properties and belongs to the Menispermaceae family. Herbicidal potential of aerial parts of T.tuberculata on germination and seedling growth of rice (Oryza sativa L.) and two rice weeds, barnyardgrass (Echinochloa crus-galli L.) and weedy rice (Oryza sativa L.complex) were evaluated. Six concentrations of methanol and water extract (3.12, 6.25, 12.5, 25, 50, and 100 g L−1) were compared with the control (distilled water). The magnitude of the phytotoxicity effects at the same concentration levels in the test plants was dependent on the source of the extract (either leaf or stem) and types of solvent (water or methanol). Leaf extract was found to have greater suppressive property than the stem extract and the methanol extracts of leaf and stem were present in higher phytotoxic compared with respective water extracts. The gas chromatography–mass spectrometry (GC-MS) and ultra-fast liquid chromatography (UFLC) analysis confirmed methanol extracts and leaf extracts contained higher number and amount of chemical compounds than did those of the water extracts and stem extracts, respectively. Benzoic acid (highest allelopathic activity) was found in the highest concentration in the methanol leaf extract,while this compound was not identified in the water leaf extract. On the other hand, the predominant compound was orientin (lowest allelopathic activity) from stem extracts. Therefore, the herbicidal activity of each extract (leaf methanol extract, leaf water extract, stem methanol extract, and stem water extract) was dependent on their number, concentration, combination and inhibitory activity of the compounds. In the glasshouse experiments, allelopathic potential of powder and methanol extract of T. tuberculata leaf as pre emergence and post emergence (foliar spray at 14 days after sowing) applications on the growth and development of transplanted rice (Oryza sativa L. Var. MR219) and three common rice field weeds (barnyardgrass, smallflower umbrella sedge and weedy rice) were evaluated. The magnitude of the allelopathic effects at the same concentration levels in the test plants was dependent on the application methods (powder and extract),time of application (pre and post emergence), the concentration and the recipient species. The leaf powder was found to have greater suppressive property than the leaf extract.The findings also recorded much more inhibition in application of leaf extract as preemergence relative to the post emergence application (foliar spray). Field experiment which involves comparison between T. tuberculata leaf powder, commercial herbicide (Solito® (pretilachlor + pyribenzoxim) at 1 L ha-1) as positive control and no treatment (negative control) was done. The germination and biomass of weed plants were remarkably reduced in the plots receiving leaf powder treatment. Nevertheless, there was no significant difference between the leaf powder applied plots (at 2 and 4 t ha−1 doses) and those plots that received commercial herbicidal treatment in terms of reduction percentage of both parameters (the emergence and dry matter of weeds). There was a significant promotion on grain yield, straw dry weight and number of seed per panicle of rice, when treated with leaf powders and commercial herbicide compared with negative control. These results suggest that T. tuberculata contains a significant source of plant growth inhibitors. Hence, it can be used as a natural pre-emergent herbicide to suppress weeds in rice fields and for developing new herbicide based on phytotoxic compounds released by this plant.